2014
DOI: 10.5114/kitp.2014.43836
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distension pressure on endothelial injury and vasodilatation response in saphenous vein grafts: conversion of a bypass graft to a dead pipe

Abstract: IntroductionEndothelial damage caused by high pressure applied for spasm relaxation during graft preparation is one of the most plausible theories explaining early graft failure.Aim of the studyWe aimed to demonstrate the extent of endothelial damage in saphenous vein grafts distended to different pressure levels by using immunohistochemical methods and in vitro tissue baths.Material and methodsSaphenous vein grafts (SVGs) of 25 patients who underwent isolated elective CABG surgery were used in this study. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(26 reference statements)
0
8
0
1
Order By: Relevance
“…Contrarily, in EVH, sidings were clipped using an endoscopic clipper when visibility was poorer and access was more challenging, which may have contributed to the vascular clip occasionally rolling off the siding and bleeding from the distal region. To avoid injuring the GSV tissue, the tightness of the GSV was tested intraoperatively by injecting a fluid (NaCl 0.9% + heparin) at a pressure of 50-100 mm Hg [14]. Similarly to EVH, the harvested GSV needed additional surgical care and a vascular suture.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, in EVH, sidings were clipped using an endoscopic clipper when visibility was poorer and access was more challenging, which may have contributed to the vascular clip occasionally rolling off the siding and bleeding from the distal region. To avoid injuring the GSV tissue, the tightness of the GSV was tested intraoperatively by injecting a fluid (NaCl 0.9% + heparin) at a pressure of 50-100 mm Hg [14]. Similarly to EVH, the harvested GSV needed additional surgical care and a vascular suture.…”
Section: Discussionmentioning
confidence: 99%
“…Gurkan et al reported that a pressure of 300 mmHg abolished both contraction and relaxation due to endothelial and medial damage. The authors stated, "Pressures of 300 mmHg or more turn the SVG into a dead pipe" 20) . The upregulation of inflammatory biomarkers is related to the pressure value and degree of distention 21) .…”
Section: Avoiding Graft Distentionmentioning
confidence: 99%
“…Wszyscy operowani pacjenci zaliczali się do grupy średniego lub wysokiego ryzyka operacyjnego SSI na podstawie oceny skali BHIS (Broptom & Harefield Infection Score) [6]. U każdego z chorych występowały wybrane czynniki ryzyka SSI, do których należały to the great saphenous vein nor a problem with its patency during syringe administration of 0.9% NaCl with heparin through the cannula at a pressure between 50-100 mmHg (so as not to damage the tissue of the blood vessel taken) were found [7]. Because of the positive assessment of vein quality, all the blood vessels were used during CABG or OPCAB procedures as a coronary artery bypass.…”
Section: W Y N I K Imentioning
confidence: 99%
“…U chorych z obydwu grup po pobraniu materiału żylnego nie stwierdzono istotnych makroskopowych uszkodzeń żyły odpiszczelowej ani problemu z jej drożnością. Materiał sprawdzono, podając strzykawką przez kaniulę 0,9% NaCl z heparyną pod ciśnieniem między 50--100 mmHg, tak by nie uszkodzić tkanki pobranego naczynia [7]. W związku z pozytywną oceną jakości żyły, wszystkie naczynia zostały wykorzystane do zabiegów CABG lub OPCAB jako pomost aortalno--wieńcowy.…”
Section: W Y N I K Iunclassified